Zamansız Bir Görsel Kültür Ürünü Olarak Kaybedenler Kulübü - Yaşartürk, Gül (The Turkish Online Journal of Design Art and Communication, 2012)
The movie Kaybedenler Kulübü can be seen as an ordinary period film. Although the film takes place in the mid 1990's, it often has no periodic indicator or any expression pertaining to the period. Here, it is possible to say that the film has no borders between time and space. Although the events in the film take place in the 1990's, the audience, not having any idea about the film’s subject or the characters, can easily think that the events occur today due to the visual structure of the film. This choice may be considered as a tribute to the past, or can also be seen as an effort to bring the past forth into the present; to revive the past. Precisely within the framework of the unnoticed efforts, the real characters have began began to make the same program again, but not surprisingly, it does not meet sufficient interest. Because it is obvious that, the radio program is a periodic product. The said effort to revive the book of Baudrillard and Simulation Simulakrlar Ramses finds an optimistic reflection within the text entitled The Story of the Resurrection. After its removal from the tomb, the mummy of Ramses II decays throwing the researchers into great despair. Furthermore, the film does not establish the basis and conjuncture of radio programs' being popular in the 1990's and completely degrades itself into a product of “visual culture”. Usage of different framing to divide the screen and excessive usage of music to support the film results in its being solely consisting of form. In the film, it is possible to see neither the answer to the question “Why are these people losers?”, nor the connection between being a loser and the 1990's. Instead, Kaybedenler Kulübü builds its world upon the solitude of the characters and the discourse of the conservative world of men's fraternity.
Keywords: Tolga Örnek; 1990’s; Radio; 1990'lar; Radyo